2006
DOI: 10.1108/13620430610683034
|View full text |Cite
|
Sign up to set email alerts
|

The workaholism phenomenon: a cross‐national perspective

Abstract: PurposeThe purpose of this paper is to examine the workaholism phenomenon.Design/methodology/approachWorkaholism was defined as the individual's steady and considerable allocation of time to work, which is not derived from external necessities. Subsequently, it was measured as time invested in paid work, controlling for the financial needs for such an investment. Workaholism is examined from a cross‐national perspective through representative samples of the labor force in Belgium, Israel, Japan, The Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 88 publications
2
45
0
6
Order By: Relevance
“…It seems that they try to not serve the life events as boring and threatening and they usually try to make a dynamic life based on the exalted goal for themselves and their families. One other result was the difference between male and female as the rate of work holism in females was more than males that is not consistent (Snir and Harpaz;2006). To confirm this, some believe that men are more involve in the internal elements, while women are more involve in the external elements of life events.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…It seems that they try to not serve the life events as boring and threatening and they usually try to make a dynamic life based on the exalted goal for themselves and their families. One other result was the difference between male and female as the rate of work holism in females was more than males that is not consistent (Snir and Harpaz;2006). To confirm this, some believe that men are more involve in the internal elements, while women are more involve in the external elements of life events.…”
mentioning
confidence: 80%
“…However, there have been a few internal and external researches in this area and the author points to some researches in which two concepts of hardiness and addiction are presented as it was specified that work holism itself is a subconcept of addiction in its general form. Snir and Harpaz (2006) suggested that the probability of men works holism is more than women. Mohammad talebi (2008) in has study show the relationship between the organizational culture and work holism, Asgari, Mostafa (2002) has studied the relationship between hardiness and attachment style with the preparation for addiction that he obtained a negative and significant correlation between the hardiness and attachment with International Letters of Social and Humanistic Sciences Vol.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a cross-national study workaholism was found to be primarily a male phenomenon (Snir & Harpaz, 2006). Wharton and Blair-Loy (2002) state that employed women in the industrialized world continue to bear more responsibility for family and children than do their male counterparts so they are more often considered candidates for a part-time work.…”
Section: Background Predictorsmentioning
confidence: 97%
“…Furthermore, workaholism was associated with low levels of emotional well-being and high levels of psychological distress. In addition, workaholism was associated with high levels of psychosomatic symptoms and physical health complaints which have been linked to workaholics' not getting enough leisure time, physical exercise, and sleep (see also Burke, 2000;Ng, Sorensen, & Feldman, 2007;Robinson, 2000;Snir & Harpaz, 2006). Consequently, workaholism is not a positive characteristic indicating a healthy passion and enthusiasm for one's work, but an unhealthy characteristic that can have ruinous consequences for an individual's emotional, social, and physical well-being.…”
Section: Perfectionism and Workaholismmentioning
confidence: 99%